2004
DOI: 10.1158/0008-5472.can-03-0124
|View full text |Cite
|
Sign up to set email alerts
|

E6 and E7 Oncoproteins Induce Distinct Patterns of Chromosomal Aneuploidy in Skin Tumors from Transgenic Mice

Abstract: Inactivation of the tumor suppressor genes p53 and Rb are two of the most common genetic alterations in cancer cells. We use a mouse model to dissect the consequences of compromising the function of either of these genes on the maintenance of genomic stability. Thirteen cell lines established from skin tumors of mice expressing either the E6 or E7 oncoprotein of the human papillomavirus (HPV) type 16 under control of the keratin 14 promoter were analyzed by comparative genomic hybridization, spectral karyotypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 62 publications
2
35
0
Order By: Relevance
“…WT tumors that were used in the prior study analysis (25) and found that early and late passages show the same cytogenetic changes as described previously (data not shown). Although CGH analysis of DNA extracted directly from the tumor mass avoids the potential concern for tissue culture artifacts, it raises the concern that cytogenetic abnormalities might be missed if the fractional content of the tumor cell type over normal and/or stromal cells is insufficient.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…WT tumors that were used in the prior study analysis (25) and found that early and late passages show the same cytogenetic changes as described previously (data not shown). Although CGH analysis of DNA extracted directly from the tumor mass avoids the potential concern for tissue culture artifacts, it raises the concern that cytogenetic abnormalities might be missed if the fractional content of the tumor cell type over normal and/or stromal cells is insufficient.…”
Section: Discussionsupporting
confidence: 67%
“…These include K-ras, ephrin receptors B6 and A1, and transforming growth factor-a (TGF-a). K-ras, a commonly mutated protein in cancer, is an interesting target; however, in our previous studies, no up-regulation of this gene was observed in the K14E6 WT carcinomas (25). The ephrin receptors B6 and A1 are part of the receptor tyrosine kinase family of ephrin receptors.…”
Section: Discussionmentioning
confidence: 88%
“…Studies are in progress to investigate this in raft culture models of HPV infection. However, these studies are particularly intriguing when one considers the effects of E6 and E7 upon mitosis, where both have been shown to separately induce mitotic abnormalities when stably expressed in cultured cell lines or cells derived from transgenic mice (17,38,45). Further dissection of the role of each protein showed that when each protein is transiently expressed, only E7 results in immediate chromosomal abnormalities (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…These observations have led to development of animal models of virus-induced epithelial cell carcinomas for understanding oncogenic mechanisms in susceptible tissues. Transgenic (TR) mice expressing E6 or E7 protein of high-risk Human papillomaviruses (HPVs) or the SV40 Large T-Antigen (SV40 T-Ag) reveal that viral oncogenes induce epithelial cell cancers by interfering with mechanisms that regulate proliferation and programmed death of epithelial cells Schaeffer et al, 2004;Schreiber et al, 2004). Although significant in-roads have been made in development of anticancer agents, few therapies with proven efficacy are available for highly aggressive epithelial cell carcinomas and for majority of these patients, prognosis following diagnosis is poor (Vilchez and Butel, 2004;Young and Rickinson, 2004;Hughes, 2005).…”
Section: Introductionmentioning
confidence: 99%